Socioeconomic determinants of the employment/income capacity of MSMEs in South-west Nigeria - Ayobade, Adebowale; Ajuwon, Oluseye; Saibu, Olufemi (International Journal of Publication and Social Studies, 2024)
This paper analyzed socioeconomic characteristics of micro, small, and medium-sized enterprises (MSMEs) that have implications for employment and income generation potentials in Osun and Oyo states of southwestern Nigeria. The paper used multistage sampling technique to identify and collect data from 1020 SMEs, analyzed using descriptive and inferential statistical technique. The result showed that gender bias inhibits both income and employment generating potentials, with male dominance over female dominance hindering female ability to pivot and reduce poverty among business owners while age has a significant positive effect on employment generation but not a significant factor in generating revenue. Marital status has a negative effect on job creation but not significant in their income-generating potential. Labour regulation and access to credit are the two most significant institutional factors affecting MSMEs' income and employment generating potentials. Religion does not appear to be a significant component in boosting income-generating potential and education is seen as having a negligible negative influence. Financial difficulties are the greatest restriction for MSMEs in Osun and Oyo states while taxation and government policy have a positive impact on income generation potential, as compliance with official rules encourages firms to explore government incentives.